Siva gos Anser anser - Bordjan, Dejan (Acrocephalus, 2018)
In December 2017 and January 2018 more than 1000 Greylag Geese were present at the Medvedce reservoir, with up to 1,928 individuals counted on 4 Jan 2018. On that day, 494 White-fronted Geese were also observed. This is the highest number of Greylags counted so far in Slovenia and the highest number of any geese since the end of the 1990s.
Keywords: Anser anser; ornitologija; ptice; siva gos